Introduction to the special issue: Media use and selectivity - Bilandzic, Helena and Krotz, Friedrich and Rössler, Patrick (comm, 2006)
Abstract An expanding media universe confronts readers, viewers, and users with an abundance of media content that, for the most part, will not be used by the audience, and will, in many cases, not even be considered for use. Selecting what to use and not to use is functional in avoiding information overload (Carlson, 2003) or ‘technostress’ (Rosen and Weil, 1997), but, at the same time, necessary to make use of the media environment. The selection of media initiates gratifications, serves particular functions, enables certain effects, all depending on the perspective. Media use and selectivity constitute a field of remarkable tradition in communication research. The question how individuals deal with media and why they use certain media content has been in the focus of communication research from the very beginning of empirical media research; since Lazarsfeld and his colleagues conducted their radio research projects (Lazarsfeld and Stanton, 1944), which included Herzog's (1944) widely cited study on daytime serial listeners. Thinking about media use reached a first prime with the emergence of Uses and Gratifications approaches; an abundance of studies about ‘what people do with the media’ have been published during the golden years of Uses and Gratifications in the 1970s and 1980s. Bryant and Miron (2004) identified Uses and Gratifications – along with Agenda Setting – as the approach most frequently used in three communication journals from 1956 through 2000.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUxNS9jb21tdW4uMjAwNi4wMTc